Morpho-Physiological Assessment of Tomato and Bell Pepper in Response to Nutrient Restriction - Lucas Aparecido Manzani Lisboa; Fernando Shintate Galindo; Paulo Humberto Pagliari; João Igor Ussifati Pessoa Goncalves; Matheus Haruichi Okazuka; Matheus Luís Oliveira Cunha; Paulo Alexandre Monteiro de Figueiredo (Stresses, 2024)
The aim of this study was to investigate the morpho-physiological responses of tomato and bell pepper plants when specific nutrients were restricted. The study was conducted in a greenhouse under controlled environmental conditions and used hydroponic solution as the growth medium, with the nutrient solution being replaced as needed. Treatments consisted of a control treatment that included all nutrients at optimal concentrations and the suppression of magnesium (Mg), boron (B), zinc (Zn), and iron (Fe) for both tomato and bell pepper. The experimental design followed a completely randomized design, with a 2 (crops) × 5 (treatments) factorial scheme replicated four times. The results of this study showed that suppression of Fe had the most pronounced negative effect on the morphology and physiology of tomatoes and bell peppers and caused a reduction in parameters associated with gas exchange, leading to the development of interveinal chlorosis in the leaves. The suppression of Mg had the second most notable negative effects, with similar deficiency symptoms observed in the plant leaves as observed for the absence of Fe. While the suppression of B and Zn were less prominent compared to Fe and Mg, they still resulted in tissue malformation in the shoot apices and reductions in gas exchange and negatively impacted the morphological parameters evaluated. Therefore, our study provided important insights on how Mg, B, Zn, and Fe depletion affects tomato and bell pepper physiology and its impacts on tomato and bell pepper morphology.